(untitled) (Ustozlar uchun, 2026)
Classical detective fiction is traditionally centered on a rational and authoritative detective figure who uncovers truth through logical investigation and restores social order. However, contemporary crime fiction increasingly departs from this model by questioning the stability of truth and the authority of institutions. This article examines the absence of the traditional detective in modern crime fiction through a case study of Gillian Flynn’s novel Gone Girl (2012) and its film adaptation directed by David Fincher (2014). Drawing on narrative theory and adaptation theory, the study explores how investigative authority is redistributed from a single detective figure to unreliable narrators, media institutions, and the audience.